Verdier i barnevern - Nordby, Halvor; Halsa, Astrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"Values in Child Welfare Service discusses how child welfare services are influenced by social, cultural and personal values. The primary objective of this anthology is to contribute to debate on how frameworks, ideologies and moral understandings can and should have an impact on child welfare services' work on behalf of vulnerable children and youths. The book is divided into two main sections. The chapters in the first part look at system-based guidelines for practical and theoretical understandings of core concepts in professional child welfare practices. The chapters in the second part focus more directly on empirical examinations of how values and conflicts of values arise in practice-oriented child welfare education and actual child welfare work. The chapter authors focus on central values in child welfare from a variety of professional perspectives. In this way, the book emphasizes the importance of understanding child welfare work as a delimited, yet also multi-disciplinary value-based practice."